2002
DOI: 10.1097/00005392-200204000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Management Of Stage T1 Transitional Cell Carcinoma Of The Bladder

Abstract: High grade stage T1 transitional cell carcinoma is a highly malignant tumor. Complete resection followed by immediate mitomycin C instillation and 6 weekly BCG instillations results in an acceptably low recurrence and progression rate. Rigorous long-term surveillance and continuous reconsideration of radical cystectomy in concordance with the evolution of the disease are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 121 publications
0
54
1
3
Order By: Relevance
“…In accordance, others have found that the false-positive rates vary greatly between institutions [13,14], 4–53%, which might be the result of a different PDD qualities [15]. Similarly, the rate of tumor residuals found at second look TURBT also varies greatly among hospitals and urologists, 27–78% [16,17,18]. Many of the residual tumors (54%) are found outside the primary resection site [19] which would suggest that tumors can be overlooked by urologists.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In accordance, others have found that the false-positive rates vary greatly between institutions [13,14], 4–53%, which might be the result of a different PDD qualities [15]. Similarly, the rate of tumor residuals found at second look TURBT also varies greatly among hospitals and urologists, 27–78% [16,17,18]. Many of the residual tumors (54%) are found outside the primary resection site [19] which would suggest that tumors can be overlooked by urologists.…”
Section: Discussionmentioning
confidence: 53%
“…Third, the bladder volume is maintained at 50–75% capacity during TURBT to improve the identification of carcinoma in situ. In addition, overfilling of the bladder increases the risk of bleeding which impairs inspection of the bladder mucosa [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Progression to muscle invasion occurs in about 15-20% of cases [12], taken all different groups of pTa (PUNLMP, NILGC, NIHGC). Especially, NIHGC has a high rate of progression that varies between 23 and 65% in different studies [20,40]. pT1 tumors progress in up to 30% of cases [16].…”
Section: Discussionmentioning
confidence: 99%
“…PTa bladder cancers have a variable recurrence rate and progression [13,16,20,40]. In papillary urothelial neoplasm of low malignant potential (PUNLMP) or non-invasive papillary urothelial carcinoma low grade (NILGC), recurrence varies from 25 to 70%, and few progress towards higher grade or invasive tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus Calmette-Guérin (BCG) is a well-known anticancer agent for intravesical instillation the effectiveness of which has been established for patients with carcinoma in situ (CIS) or superficial non-muscle-invasive high-grade bladder tumors [5,6]. However, this immunotherapy is not generally indicated for single or multiple low-grade tumors.…”
Section: Introductionmentioning
confidence: 99%